Recent Advances on Copper-Catalyzed C–C Bond Formation via C–H Functionalization - Almasalma, Ahmad A.; Mejía, Esteban (Synthesis, 2020)
Reactions that form C–C bonds are at the heart of many important transformations, both in industry and in academia. From the myriad of catalytic approaches to achieve such transformations, those relying on C–H functionalization are gaining increasing interest due to their inherent sustainable nature. In this short review, we showcase the most recent advances in the field of C–C bond formation via C–H functionalization, but focusing only on those methodologies relying on copper catalysts. This coinage metal has gained increased popularity in recent years, not only because it is cheaper and more abundant than precious metals, but also thanks to its rich and versatile chemistry.1 Introduction2 Cross-Dehydrogenative Coupling under Thermal Conditions2.1 C(sp3)–C(sp3) Bond Formation2.2 C(sp3)–C(sp2) Bond Formation2.3 C(sp2)–C(sp2) Bond Formation2.4 C(sp3)–C(sp) Bond Formation3 Cross-Dehydrogenative Coupling under Photochemical Conditions3.1 C(sp3)–C(sp3) Bond Formation3.2 C(sp3)–C(sp2) and C(sp3)–C(sp) Bond Formation4 Conclusion and Perspective
Keywords: copper; cross-dehydrogenative coupling; C–H derivatization; oxidants; photocatalysis